Neuromuscular and sensory disturbances in patients with well treated coeliac disease. Issue 4 (1st April 2003) - Luostarinen, L; Himanen, S-L; Luostarinen, M; Collin, P; Pirttilä, T
Abstract : Objectives: A body of evidence shows that coeliac disease is associated with protean manifestations outside the intestine, and neurological disorders are well recognised. However, it remains obscure whether there are signs of clinical or subclinical nervous system involvement even in patients adopting an adequate gluten free diet. The aim of this study was to assess in a controlled study whether patients with treated coeliac disease carry an increased risk for neuropathy and characterise the type of possible neuropathy. Methods: Electroneuromyographic findings and vibration, thermal, and tactile thresholds of 26 patients with coeliac disease and 23 patients with reflux disease were analysed. Results: Six (23.1 %) coeliac disease patients and one (4.3 %) reflux disease patient showed findings of chronic axonal neuropathy in quantitative needle EMG. In addition, two coeliac disease patients showed findings suggestive for myopathy. There were no significant differences in warm, cold, or vibration thresholds between the groups but means of heat pain thresholds and tactile thresholds were significantly higher in coeliac patients than in controls. Conclusion: An increased occurrence of axonal neuropathy was observed in well treated coeliac disease. This further indicates that neurological manifestations occur even in patients without overt malaborption.